2022
DOI: 10.1186/s41182-022-00484-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sexual partnership among adolescent boys and young men in Ghana: analysis of the 2003–2014 Ghana Demographic and Health Survey

Abstract: Background Multiple sexual partnership (MSP) is a major cause of HIV/AIDS epidemic and unplanned pregnancies in sub-Saharan Africa. We investigate how individual, household, interpersonal, community and structural factors correlate with multiple sexual partnership of adolescent boys and young men in Ghana. Methods We pooled secondary data from the 2003, 2008 and 2014 Ghana Demographic and Health Surveys (GDHS). Analytic sample of 1422 males aged 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Among men in Sub-Saharan Africa, key barriers against male HIV testing have been closely associated with a lack of HIV knowledge, HIV clinic location or practices, con dentiality issues, fear of doing a HIV test and discovering a positive status (16). Overall, previous research in Ghana indicates that AYA possessing secondary or higher education, or emanating from the richest wealth status had greater odds of engaging in multiple sexual partnerships than those who were poor with primary or no education (17). Similarly, age and marital status were signi cantly associated with HIV testing among Ghanian AYA involved in another study (18).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Among men in Sub-Saharan Africa, key barriers against male HIV testing have been closely associated with a lack of HIV knowledge, HIV clinic location or practices, con dentiality issues, fear of doing a HIV test and discovering a positive status (16). Overall, previous research in Ghana indicates that AYA possessing secondary or higher education, or emanating from the richest wealth status had greater odds of engaging in multiple sexual partnerships than those who were poor with primary or no education (17). Similarly, age and marital status were signi cantly associated with HIV testing among Ghanian AYA involved in another study (18).…”
Section: Introductionmentioning
confidence: 76%
“…Moreover, the study's framework suggests it lacks the capacity to conclusively establish or imply a causal connection between HIV PrEP, acceptance of HIV PrEP, HIV testing, and socio-demographic predictors because of its crosssectional design. Given that this sample utilized for this study were derived from the larger men's dataset (ages 15-59) that used general men's questionnaire, the item pool in the measure may have been too broad or rigorous or not tailored speci cally for the youngest group (ages [15][16][17][18][19] which may impact their responses. Likewise, the non-inclusion of female AYA in Ghana denies the study the gender implications and nuances that may have been crucial to comprehensively evaluate sexual reproductive health outcomes among AYAs in Ghana for both genders.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
“…According to Yeboah et al [ 4 ] and Nyarko and Potter [ 5 ], serial fathering is on the rise regardless of whether or not a man has lost his spouse. Throughout many parts of the world, divorce and having many children have been linked to having multiple fathers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…8, 2123 Little is known about the sexual partnerships of ABYM, including age-disparate sexual partnerships, although we know that multiple concurrent sexual partnerships are common. 24, 25…”
Section: Introductionmentioning
confidence: 99%
“…8,[21][22][23] Little is known about the sexual partnerships of ABYM, including agedisparate sexual partnerships, although we know that multiple concurrent sexual partnerships are common. 24,25 A South African study on the trends and correlates of HIV prevalence among adolescents aged 12-19 years in different contexts and at various stages of the epidemic examined the association between risky sexual behaviours such as early sexual debut, inconsistent condom use, substance use (alcohol and drug use), peer pressure, and sensation-seeking behaviours and HIV prevalence. 26 Results from this study indicated a statistically significant change in HIV prevalence among adolescent males over time.…”
Section: Introductionmentioning
confidence: 99%